Community research collaboration to develop a promotores-based hereditary breast cancer education program for Spanish-speaking Latinas. Issue 3 (11th June 2021) - Almeida, Rebeca; Lopez-Macha, Alejandra; Dugatkin, Tania; Joseph, Galen; Duron, Ysabel; Hurtado de Mendoza, Alejandra; D. Graves, Kristi; Fejerman, Laura
Abstract: Breast cancer (BC) is the most common cancer in Latinas and the leading cause of cancer death. Latinas tend to be diagnosed at later stages, receive poorer quality care and have a higher risk of mortality than non-Latina White (NLW) women. Among women with a genetic predisposition to hereditary BC, genetic counseling can be beneficial. Latinas participate in genetic counseling at lower rates than NLW women. The goal of this study was to develop comprehensive, culturally appropriate materials for community health educators (promotores)-led hereditary BC education program for Spanish-speaking Latinas. We developed the curriculum through feedback from 7 focus groups, with a total of 68 participants (35 promotores and 33 community members). We used a mixed-methods approach that relied on quantitative analysis of survey questions and qualitative content analysis of the focus groups transcripts. Pre and post promotores' training survey responses suggested improvement in the promotores' cancer-related knowledge. Themes that emerged from the qualitative analyses were (i) barriers to health education and/or care; (ii) importance of educating the Latino community about BC and genetics and (iii) role of the promotores. Future research will further evaluate the impact of the program in promotores' knowledge and community members' screening behaviors.